Relationships among COVID-19 causal factors perceived by children, basic psychological needs and social anxiety - Higinio González-García; Leandro Álvarez-Kurogi; Joel Prieto Andreu; Javier Tierno Cordón; Rosario Castro López; Jesús Salas Sánchez (PeerJ)
Background The pandemic caused by COVID-19 had a great impact on our society as the lives of children have been affected, as well as their psychological health and social anxiety. Objective To examine whether COVID-19 causal factors perceived by children predicted basic psychological needs and social anxiety, and if basic psychological needs predicted social anxiety. Methods A sample of 58 schoolchildren (Mage = 10.18; SD = 0.77; 36 boys, 22 girls) participated in the study and completed a series of self-report measures. The relationship between the study variables was examined using partial least square path modelling (PLS-PM). Results Social distancing and protection were found to significantly reduce competence satisfaction. Perceived psychological impact significantly negatively predicted relatedness satisfaction and significantly positively autonomy frustration and competence frustration. Perceived psychological impact significantly negatively predicted anxiety in the interaction with the opposite sex. Autonomy satisfaction significantly positively predicted anxiety in the interaction with the opposite sex. Autonomy frustration significantly positively predicted anxiety in public speaking interaction with teachers, significantly positively anxiety in the interaction with the opposite sex, significantly positively anxiety of being embarrassed or ridiculed and significantly positively anxiety in the interaction with strangers. Conclusion Perceived psychological impact was the causal factor that revealed a higher impact on basic psychological needs. As such, it is important to take measures with children in pandemic situations to minimize this variable. On the other hand, Autonomy frustration revealed a higher impact on social anxiety. Thus, it is necessary to emphasize autonomy in children respecting the restrictions imposed to minimize the impact of social anxiety.